PERAN SUPERVISI PENDIDIKAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DAN PEMANFAATAN TEKNOLOGI DI SMP IT AL-MADANI - Sahrul Adi Amanatulloh; Kurnia Permata Nur Aisah; Soedjono Soedjono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Technological advances have changed the way of learning and teaching, enabling online learning and access to information quickly. However, not all teachers have enough skills to use technology in teaching. Although there is an attempt to integrate technology, there are still many obstacles in SMP it Al-Madani, such as lack of training for teachers, limited facilities and infrastructure, as well as low motivation to adapt. This study aims to fill out the deficiency of knowledge of how the supervision of education can overcome these obstacles and accelerates the utilization of technology in SMP it is al-Madani. This research uses qualitative descriptive method to describe the role of education supervision in improving the quality of learning and utilization of technology. The subjects of the study include teachers, educational supervisors, and school management involved in supervision and technility implementation. Data collection techniques include in-depth interviews, participatory observations, and documentation. The analysis of this research data is done with the thematic approach. The results showed that the supervision of education played an important role in guide to overcome the barriers, such as the lack of digital literacy, the minimal technology-based training, limitations of facilities, and low motivation. Effective supervision provides directed guidance, supporting collaboration, and encouraging policy development that supports technology integration. Research recommendations include increased training, provision of technology facilities, formal policy development, and increased digital literacy of teachers. With a planned supervision strategy, learning quality is expected to increase, creating more interactive and relevant learning experience in the digital era.